Effective CpG DNA delivery using amphiphilic cycloamylose nanogels. (13th October 2014) - Tahara, Y.; Yasuoka, J.; Sawada, S.; Sasaki, Y.; Akiyoshi, K.
Abstract : Native CpG oligodeoxynucleotides induce inflammatory immune responses through cytokine production by their effective cell uptake with amphiphilic cationic cycloamylose nanogels. Abstract : Unmethylated CpG oligodeoxynucleotides induce inflammatory immune responses through cytokine production and have attracted increasing attention as an immunostimulator. However, there remains a challenging issue of the use of 'native CpG DNA'. In the present study, we prepared cationic nanometer-sized gels (nanogels) consisting of cycloamylose modified with cholesterol and diethylaminoethane to form hydrophobic cross-linking points and to add positively charged groups, respectively. The cationic nanogels and native CpG DNA formed nanometer-sized complexes. Complexes of native CpG DNA with cationic nanogels delivered native CpG DNA to macrophage-like cells and induced cytokine production. In addition, complexes of negative control oligonucleotides with cationic nanogels did not induce cytokine production, and the induction of cytokines using complexes of phosphorothioate-modified CpG with cationic nanogels was lower than that of native CpG DNA. These results suggest that the complex of native CpG DNA with cationic nanogels is a promising strategy for nucleic acid adjuvants.